2018
DOI: 10.1177/0047281618775908
|View full text |Cite
|
Sign up to set email alerts
|

Developing Strategies for Success in a Cross-Disciplinary Global Virtual Team Project: Collaboration Among Student Writers and Translators

Abstract: This article reports on a qualitative study of strategies and competencies used by technical communication and translation students to address challenges inherent in global virtual team collaboration. The study involved students from three universities collaborating in virtual teams to write and translate instructional documents. Qualitative content analysis of students' reflective blogs and team transcripts was used to examine their experiences while collaborating. Students faced challenges related to communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Despite the technological sophistication of many students, studies show they are not prepared for online collaboration, because the aspects of virtuality and internationality add additional challenges to collaborating, for example, in communication, technology use, leadership, project management, and cultural diversity (Cleary et al, 2019; Robey et al, 2000). There is, thus, a need to train IOCCs for effectively working in international VTs (Ford et al, 2017; Wang & Haggerty, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the technological sophistication of many students, studies show they are not prepared for online collaboration, because the aspects of virtuality and internationality add additional challenges to collaborating, for example, in communication, technology use, leadership, project management, and cultural diversity (Cleary et al, 2019; Robey et al, 2000). There is, thus, a need to train IOCCs for effectively working in international VTs (Ford et al, 2017; Wang & Haggerty, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This study analyses studies reporting competencies involved in IOC. Research on this topic is fragmented, as most studies focus on specific moderators involved in IOC such as knowledge sharing and trust (Alsharo et al, 2017), communication strategies, trust formation, leadership, technology selection and use, and culture (Cleary et al, 2019; Robey et al, 2000). Few studies cover a broad enough set of IOCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of virtual teamwork projects in innovation activities, the empirical studies on student innovation capability and propensity to innovate in a virtual environment are largely unexplored. Virtual team project literature largely focuses on cultural intelligence, success in the global environment, team performance and fuzzy front-end of innovation in virtual teams (Cleary et al , 2019; Dibble et al , 2019; Gressgård, 2011; Chamakiotis et al , 2020). For instance, Cleary et al (2019) showed that the missing link between strategies for success in a global virtual team project among students includes leadership, communication and technology.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most remarkable trends has been the coming of era Industry 4.0, characterized by the rise of complex interactive and integrated manufacturing systems (Roblek, Meško, & Krapež, 2016;Tareva & Tarev, 2018). This interconnectedness is creating new opportunities for cross-industry relationships and entails collaborative engineering practices (Cleary, Slattery, Flammia, & Minacori, 2018;Jeyaraj, 2017). The idea behind the collaborative nature of gaining knowledge is that it is "never a solitary act but a community affair" (Rifkin, 2013, p. 247).…”
Section: Introductionmentioning
confidence: 99%